ANALISIS KEUNTUNGAN USAHATANI ANTAR POLA TANAM DI LAHAN SAWAH DESA TATA KARYA KECAMATAN ABUNG SURAKARTA KABUPATEN LAMPUNG UTARA - Novita Setiani; Wan Abbas Zakaria; Rabiatul Adawiyah (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2015)
The aims of this research are to figure out the profit of each crop system at Tatakarya Village Abung Surakarta Subdistrict of North Lampung Regency. Primary and secondary data were collected in this reserch. The sampling used Simple Random Sampling. Amount of respondent consist of 24 farmers on rice-cassava crop system, 16 farmers on rice- rice- corn crop system, and 10 farmers on rice- rice- peanut crop system. This research took more and less than three months, started from April to June 2014. The result of this research showed that the average profit of agriculture business on rice-cassava crop system was Rp17,549,768.47/ha/year, on rice-rice-corn crop system was Rp27,225,066.06/ha/year, and rice- rice- peanut crop system was Rp36,933,811,55/ha/year. The production cost had significant influence of profit on the each crop system. The most profit crop system was rice- rice- peanut crop system with R/C ratio as big as 2.39 which means that for each Rp1.000,00 cost could get a profit of Rp1,390.00. Key words: cost, crop system, profit